KAJIAN SIFAT TRANSFER PANAS BAHAN MAKANAN BERPATI SELAMA PROSES PENGGORENGAN (The Study of Heat Transfer Properties Starchy Foods During Frying Process) - Suoriyanto .; Ridwan Lutfiadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2005)
Frying is a foods cooking method that using hot fat or oil as the heat transfer media. During frying, at foods occured heat transfer process from the oil to the surface materia! and fitrthermore from the surface to the inside material. The ''ehcity of the heal transfer process in material influenced (he frying process and the quality of prvduct. The velocity of the heat transfer process the each foods was influenced by the heat transfer properties of foods. Ihe objective of this research was to study the heat transfer properties of starchy foods during the flying process. The samples used on the experiment ira.v dried dough corn powder. The dough was made of a mixture of two variety corn with different amylo.se - amyhpectm content, with variation on the composition of the mixture. Bisma variety is used as the high amylose ( low amylopectin) and Pulut (waxy) is used as the low amylase (high amylopectin).The slabs of the corn dough was fried in fresh coconut oil at 180°C using the deep flying method. The results show that the heat transfer properties of starchy foods is influenced by the tempemture of the flying process and the moistwv content of the raw material. The correlation of the heat transfer conductivity (k) and the specific heal (Cp) with the temperature of the material (T) and the water content of the material (Ka) can be formulated as : k = a+ ajl' + a.iKa and Cp =+ aT cttKa. with ai, 0C2, a>, or as and a6 were the constants pammeter that were obtained by the Hooke-.!eeves minimize method.",